Forensic neuropsychological assessment of children victims of violence - Sales , Synara Sepúlveda (2020)
Violence in its most general aspect reveals important issues, mainly related to physical, mental, social and legal consequences. Childhood violence is a public health issue, as damage is described, affecting mainly cognitive, emotional and behavioral development. Studies show damage to children's development, resulting in biochemical, functional and structural changes in the brain, resulting from the violence suffered. The objective of the article was to verify the scientific production on the impact of violence on children's development in the field of forensic neuropsychology. Therefore, the production of knowledge on the topic and the impact of maltreatment on children's neuropsychological development was analyzed. This is an integrative literature review, supported by international databases. The results demonstrate the importance of a forensic neuropsychological assessment, to detect the impacts of violence, as well as to develop prevention and action strategies, in the scope of mental health, forensics and/or legal demands and thus, devise more effective measures for this population and subsidize public risk reduction policies applied to children and adolescents. Studies are still small, which shows a wide field to be investigated.